Household latrine utilization and associated factors in semi-urban areas of northeastern Ethiopia. - Deres Asnake; Metadel Adane (PLoS ONE, 2020)
Background Latrine utilization is the actual behavior in a practice of regularly using existing latrines for safe disposal of excreta. Latrine utilization is a common problem in semi-urban areas of developing countries, including Ethiopia. Since the status of latrine utilization and associated factors among semi-urban areas of northeastern Ethiopia, including Alansha in South Wollo Zone is unknown, local data is needed in order to assess the need for planning of intervention programs for the improvement of latrine utilization to support consistent and sustained latrine utilization. This study is designed to address this knowledge gap. Methods A cross-sectional study was conducted from February to March, 2019 among 401 systematically selected households. Data were collected by trained workers using a pre-tested, structured questionnaire via face-to-face interviews and on-the-spot observations of the latrines. A systematic random sampling method was used to select participant households. Data were entered using EpiData version 3.1 and exported to Statistical Package for the Social Sciences (SPSS) version 25.0 for data cleaning and analysis. The wealth index status of participants was estimated using principal component analysis. Data were analyzed using a binary logistic regression model at 95% confidence interval (CI). From the multivariable logistic regression analysis, variables with p-value < 0.05 were taken as statistically significant and independently associated with latrine utilization. Model fitness was checked using Hosmer-Lemeshow test. Result We found that the prevalence of latrine utilization among households was 71.8% (95% CI [67.5-76.1%]) while 28.2% (95% CI [23.9-32.5%]) did not utilize latrines. About one-fifth (21.7%) of participant households were found to have a pit latrine with slab and 78.3% (311) used pit latrines without slab. The hygienic condition of the majority (82.9%) of the latrines was dirty and only 17.1% clean. Household family size from one to three persons (AOR: 3.99, 95% CI [1.20-6.24]), presence of primary or secondary school student in a house (AOR: 2.33, 95% CI [1.42-3.83]), number of years since latrine was constructed (≥ 2 years) (AOR: 1.82, 95% CI [1.12-2.95]) and a frequency of daily cleaning of the latrine (AOR: 2.19, 95% CI [1.12-4.28]) were factors significantly associated with latrine utilization. Conclusion Seven out of ten households utilized a latrine. Factors significantly associated with latrine utilization were household family size from one to three persons, presence of primary or secondary school student in the house, time since household latrine had been constructed of two or more years and daily frequency of latrine cleaning. Therefore, it is recommended that measures to promote behavioral change towards further improvement in sustainable and consistent latrine utilization should be carried out based on the evidence of the determinant factors found in this study.